Occurrence of Tachymenis chilensis chilensis (Schlegel, 1837) (Reptilia: Serpentes: Dipsadidae) and other herpetological fauna from Epu Lauquen Natural Protected Area, Neuquén, Argentina - Nenda, Santiago Javier (2017)
We report a new specimen of Tachymenis chilensis chilensis from Epu Lauquen Natural Reserve, Neuquén, Argentina. This specimen represents the northernmost voucher of T. c. chilensis in Argentina and confirms the presence of the subspecies occupying moist habitats remnants in dry areas of northern Neuquén province. Moreover, this record corresponds to the northernmost population of T. c. chilensis in a protected area in Argentina. We also found two sympatric anurans, Rhinella spinulosa and Pleurodema thaul. Both anurans also represent the first record of amphibians at Epu Lauquen Natural Reserve.